2023
DOI: 10.3201/eid2901.221151
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Booster Dose Vaccination Coverage and Factors Associated with Booster Vaccination among Adults, United States, March 2022

Abstract: A COVID-19 vaccine booster dose is intended to boost the immune system for better, long-lasting protection when the primary vaccine response decreases over time. Studies have shown that a booster increased the immune response in trial participants who completed a Pfizer-BioNTech (https://www.pfizer.com) or Moderna (https://www.modernatx.com) primary series 6 months earlier or who received a Johnson & Johnson/Janssen (https://www.jnj.com) singledose vaccine 2 months earlier (1,2).With an increased immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Notably, we found that the timing and shape of rollout, the two most important factors deciding the burden of mortality, are not associated with SES. Given that previous studies have mainly focused on overall coverage and vaccine hesitancy, rather than early uptake [e.g., (33)(34)(35)], these findings suggest that timing deserves further consideration when studying social and demographic heterogeneity. While it is intuitive that a faster vaccine rollout leads to a lower burden of disease, our results suggest that modifying the distribution and timing of early vaccine rollout for all groups can effectively counterbalance the negative effects of vaccine inequity.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, we found that the timing and shape of rollout, the two most important factors deciding the burden of mortality, are not associated with SES. Given that previous studies have mainly focused on overall coverage and vaccine hesitancy, rather than early uptake [e.g., (33)(34)(35)], these findings suggest that timing deserves further consideration when studying social and demographic heterogeneity. While it is intuitive that a faster vaccine rollout leads to a lower burden of disease, our results suggest that modifying the distribution and timing of early vaccine rollout for all groups can effectively counterbalance the negative effects of vaccine inequity.…”
Section: Discussionmentioning
confidence: 92%
“…However, in combination with or in place of vaccines, there are several combinations of alternate strategy suites which yield lower outbreak sizes. This is fortunate in the wake of recent concerns over rapidly evolving variants (Groenheit et al, 2023) outpacing vaccine advancements as well as vaccine uptake (Lu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is fortunate in the wake of recent concerns over rapidly evolving variants [76] outpacing vaccine advancements as well as vaccine uptake. [77] That is not to say however, that vaccination is not critical for controlling this disease, as studies show that vaccinations significantly reduce serious complications and deaths. [78] Current discussions in this work were focused on the number of cases during the Omicron wave, both in total and at its peak.…”
Section: Discussionmentioning
confidence: 99%
“…This is fortunate in the wake of recent concerns over rapidly evolving variants [ 76 ] outpacing vaccine advancements as well as vaccine uptake. [ 77 ]…”
Section: Discussionmentioning
confidence: 99%